(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The blasting is the predominating method o f breaking rocks in various surface and underground mines. At the same time some damaging impacts on environment are evident: noise, gas, dust, flyrock and ground vibration. The last factor is most important for safety o f constructions, buildings and various natural objects in the vicinity o f mining area. The ground vibration parameters, crucial for safety o f endangered objects have a significant correlation with charge weight and distance o f blasting. The properties o f vibration medium impact on the value o f these parameters. This study tried to associate the main vibration parameter, particle velocity with blasting parameters and properties o f vibration medium. The blast vibrations were studied in the soil o f Quaternary sediments and in Ordovician limestone in Estonian oil shale mining area in opencast and underground mines. The analysis o f measured data pointed significant correlation between vibration velocity and scaled distance from charges. The formulas and nomographs for prediction o f vibration velocity and fo r maximum permitted charge weights were elaborated fo r basic rocks and fo r soil, fo r oil shale underground and opencast mines. Using these formulas and nomographs in blast design will make possible to diminish the impact o f mine blasting on the objects located in the vicinity of mining area.